2022
DOI: 10.3390/nu14020358
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Associated Factors in Brazilian Undergraduates during the COVID-19 Pandemic

Abstract: Undergraduates may face challenges to assure food security, related to economic and mental distress, especially during the COVID-19 pandemic. This study aimed to assess food insecurity and its associated factors in undergraduates during the COVID-19 pandemic. An online cross-sectional study was conducted from August 2020 to February 2021 with 4775 undergraduates from all Brazilian regions. The questionnaire contained socio-economic variables, the validated Brazilian food insecurity scale, and the ESQUADA scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…Stress and depression were indeed a variable that causes food insecurity among students in a university [23]. This also happened to undergraduate students in Brazil [24]. However, other studies (meta-analysis) found the opposite relationship; food insecurity caused a person to experience stress and depression [25].…”
Section: Resultsmentioning
confidence: 96%
“…Stress and depression were indeed a variable that causes food insecurity among students in a university [23]. This also happened to undergraduate students in Brazil [24]. However, other studies (meta-analysis) found the opposite relationship; food insecurity caused a person to experience stress and depression [25].…”
Section: Resultsmentioning
confidence: 96%
“…Studies have shown that no less than 20 to 30 % of students gained weight during the pandemic (30,31,58,67,69) , and this was related to factors such as the male gender (33,35,50,68) , increased intake of refined carbohydrates, alcohol, fats, and take away foods (32) , increased snacking (32) , reduced sleep quality (65) , delay in meal-timing (65) , low levels of physical activity (52,65,66,67) , and food insecurity (38) . COVID-19 pandemic affected the students' abilities to attain food and increased the prevalence of food insecurity among this population (36,37,38,39,40,41,42) , with over 30% of students being food insecure in the U.S. (38,39,41) , Brazil (42) , Thailand (74) , and Australia (75) . Factors that predicted food insecurity among college students during the pandemic included loss or reduction of employment, receipt of financial aid, furlough, alterations in living arrangements and housing status, lower cooking self-efficacy, consumption of more take-out or fast food, low diet quality, pre-COVID-19 financial status, the non-White ethnicity, and closure of college campuses (38,39,40,41,42,74) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, findings from various longitudinal studies also confirmed a significant increase in body weight of college students during the pandemic (48,54,66,70) and a decrease in diet quality (54,55) . Another limitation is the use of self-reported measures, in most of the studies, to assess and determine changes in diet quality (31,32,55,60) , dietary habits (32,50,51,60) , and body weight (30,31,32,33,34,35,48,52,58,65,67,68,69) along https://doi.org/10.1017/S0007114522002604 Published online by Cambridge University Press with the prevalence of food insecurity (36,38,39,40,41,42,43,74,75) . When it comes to diet, for instance, most investigations relied on one survey administered at one-time point to measure intake during the pandemic and compare it retrospectively with pre-pandemic times, which may possibly be subjected to recall bias (31,50,55) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations